2000
DOI: 10.1128/jcm.38.12.4373-4381.2000
|View full text |Cite
|
Sign up to set email alerts
|

Results of Multiple Diagnostic Tests forMycobacterium aviumsubsp.paratuberculosisin Patients with Inflammatory Bowel Disease and in Controls

Abstract: Mycobacterium avium subsp. paratuberculosishas been incriminated as a cause of Crohn's disease (CD); however, studies to date have been relatively small and generally only used a single diagnostic assay. The objective of the study was to reexamine the association of M. avium subsp.paratuberculosis and CD using multiple diagnostic tests. Five methods were used to detect M. avium subsp.paratuberculosis infections in 439 inflammatory bowel disease (IBD) patients and 324 control subjects in the United States and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(33 citation statements)
references
References 67 publications
(46 reference statements)
3
28
0
1
Order By: Relevance
“…Similar high prevalence of MAP has been reported in Crohn's disease patients and controls by other workers. 13,17,40,41 Sensitivities of culture and ELISA were similar for the detection of MAP in humans. Sanderson et al 42 reported that culture was less sensitive as compared to PCR.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similar high prevalence of MAP has been reported in Crohn's disease patients and controls by other workers. 13,17,40,41 Sensitivities of culture and ELISA were similar for the detection of MAP in humans. Sanderson et al 42 reported that culture was less sensitive as compared to PCR.…”
Section: Discussionmentioning
confidence: 85%
“…52,53 Though Hermon-Taylor reported 28 different strains of MAP and some specific to particular species like sheep and cattle, 12 in North India, MAP 'bison type' was the most prevalent genotype in animals. 52,53 Collins et al 40 detected MAP in significantly higher numbers of patients with Crohn's disease than in controls. Similarly in this study, all the Crohn's disease patients were positive by ELISA as compared to 80.0% by culture.…”
Section: Discussionmentioning
confidence: 97%
“…However, the same ELISA method had been used by Collins et al. (2000) to test sera from Crohns’ disease and control subjects from the USA and Denmark and in that study a much higher percentage of Crohn's patients tested positive for Map by ELISA (20·7% Crohn's compared with 3·8% healthy controls).…”
Section: Evidence Of Map In Crohn's Disease Patientsmentioning
confidence: 99%
“…Interest in the disease is growing, not only because of the vast economic losses for farmers but also because of the hypothesized involvement of MAP in the etiology of Crohn disease. 2,3,6,10,12,22,28 Mycobacterium avium subsp. paratuberculosis is an intracellular pathogen that replicates in macrophages in the lamina propria and is shed into the feces during disease.…”
Section: Introductionmentioning
confidence: 99%